Whose data are they? Elementary school students’ conceptualization of data ownership and privacy of personal digital data - Agesilaou, Andria; Kyza, Eleni A. (My University, 2022)
The proliferation of information technology has enabled the emergence of different types of smart technologies, such as digitally enhanced toys and self-tracking wearable devices. Even though the rapid global spread of such devices has raised concerns about privacy, little is known about how children perceive such risks, while the children's voices on the topic are rarely heard. The broader goal of our work is to understand how children can be empowered through scaffolded inquiry experiences to reflect on their own use of smart, self-tracking devices and gain a deeper understanding of the digital infrastructure and the political economy of digital data. This study examined children's awareness of their digital data and issues of online privacy. At the same time, we examined the construct of psychological ownership in relation to children's personal digital data to further understand students’ disclosure practices. We report on data from 63 fifth and sixth grade students to investigate students’ awareness of how their tracked data could be used and their conceptualization of data ownership. To achieve this, we designed and implemented a learning module that employed the use of activity trackers by elementary school students. We collected data via individual pre- and post-implementation interviews, and group discussions during the implementations. Data were analyzed qualitatively using the theoretical lens of psychological ownership and frameworks of data literacy. Results suggest that students demonstrate ownership of self-tracked data, ignoring the shared ownership with other parties, but this is associated with their limited awareness of the complex infrastructure of the digital environment and the commercial exploitation of their personal digital data by others. Also, results showed that students employ a set of criteria to concede data ownership to others. Findings suggest that actions should be taken to help children develop a nuanced understanding of the data economy and its impact on themselves. This study provides directions for future research and can also inform efforts to design educational materials aiming to develop students’ understanding of online data privacy.
Keywords: Data literacy; Data ownership; Data privacy; Personal digital data; Self-tracking